The Role of Dragon Fruit Consumption (Hylocereus polyrhizus) against Plaque Reduction in Students at SD Negeri 106806 Cinta Rakyat, Percut Sei Tuan District, Deli Serdang Regency, Indonesia - Mangatas HP Hutagalung; Idamawati Nababan; Dhea (Community Medicine and Education Journal, 2023)
Dragon fruit contains fiber, which is good for digestion and oral health. Fiber can help clean teeth by binding to plaque and food particles that can cause gum disease. The vitamin C contained in dragon fruit is a powerful antioxidant and can help strengthen gum tissue. This can help prevent gum inflammation (gingivitis), which is the initial stage of gum disease. Because dragon fruit has a high water content, consuming this fruit can also help maintain oral moisture, which is important for healthy teeth. A dry mouth can increase the risk of plaque formation. This study aimed to determine the potential for consuming dragon fruit (Hylocereus polyrhizus) against plaque reduction in students at SD Negeri 106806 Cinta Rakyat, Percut Sei Tuan District, Deli Serdang Regency, Indonesia. This study is experimental research with a one-group pre and post-test approach. This study uses primary data obtained from measuring the degree of plaque on the teeth of research subjects. A total of 30 research subjects participated in this study, where the research subjects met the inclusion criteria. The results showed that the dental plaque scores of students at SD Negeri 106806, Cinta Rakyat, Percut Sei Tuan District, Deli Serdang Regency, decreased significantly before and after eating dragon fruit (Hylocereus polyrhizus), with a value of p=0.0001 (p≤0.05). These results indicate that there is an influence of dragon fruit consumption (Hylocereus polyrhizus) on reducing dental plaque in research subjects.